Mental health and exile: the therapeutical relation and the moral work of the medical intervention addressed to the victims of organized violence - Lurbe i Puerto, Kàtia (Sociedad y Economía, 2010)
This article approaches the issue of mental health in exile, based on the discursive analysis of the socio-biographical interviews to one of the beneficiaries of the mental health center specialized in the sequels of violence, EXIL-Barcelona and of the focus interviews to its staff. First, it examines the profane etiological narratives and the constituent elements of the healthcare path followed up to a violence-specialized mental healthcare center in Spain. It goes on to analyze the center’s therapeutics. The article explores the processes of subjectivation of organized violence, whose harmful sequels EXIL-Barcelona seeks to relieve by means of a therapeutic that promotes a model of citizenship. The conclusions emphasize the moral work underlying ars medicus.